Kondisi Sosial Keluarga terhadap Motivasi Beragama Mahasiswa BPI Stambuk 2019 - Alvi, Illisa; Madya, Efi Brata (LP. Ma'arif Janggan Magetan, 2023)
This study aims to analyze the effect of family social conditions on the religious motivation of BPI Stambuk 2019 students. Social family conditions include factors such as inherited religious practices, religious communication, religious support, role models, and the level of religious conflict in the family. The research method used is a qualitative approach with a case study method. Data were obtained through in-depth interviews with 15 students from various BPI Stambuk 2019 student study programs. The results showed that family social conditions had a significant influence on students' religious motivation. Inherited religious practices, open religious communication, religious support, and role models in the family are positively related to high levels of religious motivation in college students. However, the level of religious conflict in the family can affect students' religious motivation. This research provides a deeper understanding of how family social conditions affect students' religious motivation, so that the role of the family in providing support and a conducive environment in religious matters becomes increasingly important.